The Influence of Individual Skills, Education, and Technological Development on the Digital Literacy of Islamic Religious Education Teachers - Sallima Nur Aliana Rambe; Muhammad Fadhli (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The purpose of this study is to analyze the effect of implementing the Reciprocal Teaching model in Fiqh learning on students’ learning independence within the Office of the Ministry of Religious Affairs of Labuhanbatu Regency. The Reciprocal Teaching model emphasizes four main strategies, namely summarizing, questioning, clarifying, and predicting, which enable students to play an active role in the learning process. This study employed a quantitative approach with a survey design. The population consisted of Islamic Religious Education (PAI) teachers at the elementary school level under the supervision of the Ministry of Religious Affairs of Labuhanbatu Regency, totaling 310 teachers, with a sample of 169 respondents determined using the Krejcie and Morgan table through a systematic sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS. The results of the study indicate that the research instrument is valid and reliable based on outer loading, AVE, Cronbach’s Alpha, and Composite Reliability tests. The coefficient of determination test results show that the independent variables explain 80.1% of the variance in the dependent variable. The hypothesis testing results reveal that variable X1 (individual skills) and X3 (technological development) have a positive and significant effect on Y (learning independence), while variable X2 (education) does not have a significant effect.